Correlation of Macrozoobenthos Diversity Index with Physico-Chemical Factors in Lake Toba, Toba Samosir Regency - Sinambela, Masdiana; Simangunsong, Mariana; Simorangkir, Andreas; Harahap, Arman (International Journal of Science, Technology & Management, 2023)
This study aims to determine the macrozoobenthos in Lake Toba, Toba Samosir Regency. This research was conducted from May to July 2018. Determination of research stations based on environmental baseline consisted of 4 stations, namely station 1 in Lumban Binanga Laguboti village, station 2 in Lumban Bul-bul Balige, station 3 in Lumban Binanga Sigumpar, and station 4 in Hutagaol Sigumpar. Samples were taken using Eckman Grab at 3 times at each station. The macrozoobenthos found consisted of two classes, three orders, eight families, 15 species with a total of 565 individuals. The species found were Brotia subgloriosa, Brotia peninsularis, Brotia castulata, Pomacea diffusa, Pomacea paludosa, Filopaludina polygramma, Filopaludina sp., Melanoides tuberculata, Lymnaea sp., Emilia sp., Corbicula sumatrana, Corbicula fluminea, Corbicula japonica, Pilsbryoconcha exilis, and Anodonta sp.. The macrozoobenthic species with the highest number of individuals was Corbicula sumatrana with 141 individuals and the least was Lymnea sp. by 1 individual. The macrozoobenthos ecological analysis included the average density of 2260, the average diversity index of 1.282, the average uniformity index of 0.633, and the average dominance of 0.390. Then correlated with physico-chemical factors using Pearson correlation (r). Correlation of diversity index with physico-chemical factors from the strongest to the weakest starting from depth and phosphate, turbidity, temperature, pH, BOD, and DO.